PENERAPAN SISTEM APLIKASI PELAYANAN KEPEGAWAIAN (SAPK) BERBASIS ONLINE PADA BADAN KEPEGAWAIAN DAERAH KOTA PEKANBARU - sufi, wasiah; herlinda, dwi (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2017)
This research was conducted at the office of the Badan Kepegawaian Daerah of Pekanbaru. Based on their initial observations of problems in implementing Employment Service Application System (SAPK Online) at the Badan Kepegawaian Daerah of Pekanbaru.in terms of human resources mampun Technology. This study focuses on the Implementation of E-Government through Employment Service Application System (SAPK Online): (1). To Knowing how the implementation of E-Government by using the Employment Service Application System (SAPK Online) at the Badan Kepegawaian Daerah of Pekanbaru.. (2). For Knowing the factors inhibiting the implementation of E-Government by using the Employment Service Application System (SAPK Online) at the Badan Kepegawaian Daerah of Pekanbaru.. This study is a qualitative study with the primary objective to describe and depict in detail and depth about how the implementation of E-Government in personnel administration through the Employment Service Application System (SAPK Online). Then the data analysis techniques used in this research was qualitative descriptive analysis, which is a technique that tries to describe things that are special to the data obtained through observation, interviews and documentation so that a qualitative data, to be analyzed further to become a conclusions according to the indicators that have been determined by the authors.